ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN E-FILING OLEH WAJIB PAJAK - Kathleen Wiratan; Karina Harjanto (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2018)
The purpose of this research is to analyze the influence of perceived usefulness, perceived ease of use, security and privacy, readiness of technology information, user’s satisfaction towards the use of e-Filing. This research uses a primary data. Respondents are the individual taxpayers who report SPT Tahunan using e-Filing and register in the Tax Office (KPP) Madya and Pratama in Tangerang and South Tangerang City. There are 112 respondents in this study. The sampling technique used is convenience sampling. Data analysis in this research uses multiple linear regression with SPSS 25 Program. The results of this study indicate that: (1) perceived usefulness has influence on the use of e-Filing, (2) perceived ease of use has influence on the use of e-Filing, (3) the security and privacy doesn’t have influence on the use of e-Filing, (4) readiness technology information doesn’t have influence on the use of e-Filing, (5) user’s satisfaction has influence on the use of e-Filing, (6) perceived usefulness, perceived ease of use, security and privacy, readiness technology information, user’s satisfaction have influence simultaneously on the use of e-Filing.